Adverse childhood experiences and their association with health-harming behaviours and mental wellbeing in the Welsh adult population: a national cross-sectional survey. (November 2016) - Ashton, Kathryn; Bellis, Mark; Hughes, Karen
Abstract: Background: Globally, an increasing body of evidence has identified the detrimental effects that adverse childhood experiences (ACEs) can have on health across the life course. ACEs include suffering maltreatment in childhood and growing up in dysfunctional family environments. This study aimed to measure the prevalence of ACEs and their association with adult health in Wales, to inform prevention and early intervention in policy and practice. Methods: A face-to-face cross-sectional survey of adults (aged 16–69 years) was undertaken in Wales in 2015. A sample size of 2028 individuals (50·2% women) was achieved by use of stratified sampling methods (49·1% compliance rate). Respondents were asked a validated ACE questionnaire and questions about current health-related behaviours with computer-assisted personal interviewing. Although self-reporting bias is a limitation of this approach, it replicates ACE methodology undertaken internationally. Prevalence of ACEs was calculated, and adjusted to Welsh population estimates. Adjusted odds ratios for risks of health-related outcomes associated with ACEs were calculated, controlling for sex, age, deprivation, and ethnicity. Modelling estimated the reduction in prevalence of poor health-related outcomes that could be seen if ACEs had not been present. Findings: For every 100 adults in Wales, 47 had at least one ACE during their childhood and 14 experienced four or more. After correcting for sociodemographics, ACE counts predicted health-harming behaviours (four or more ACEs vs none)—eg, violence victimisation (adjusted odds ratio 14·2, 95% CI 9·1–22·1; p<0·0001), high-risk drinking (4·4, 3·1–6·4; p<0·0001), and low mental wellbeing (4·7, 3·4–6·4; p<0·0001). Furthermore, modelling suggested that health-harming behaviours and low mental wellbeing nationally could be attributed to ACEs. Interpretation: Prevention of ACEs and support for those exposed to ACEs to develop resilience is essential to improving the health of adults in future generations. Our analyses measured associations rather than causation and there might be unmeasured confounders not accounted for. Nonetheless, results from this study can be used to highlight the prevalence of ACEs in Wales and their association with health in later life. Policies such as the Well-Being and Future Generations Act (Wales) 2015 provide the legitimacy for collective targeted activity towards the primary prevention of ACEs. Funding: Public Health Wales.